SISTEM INFORMASI PENJUALAN KULINER PADA KEDAI LINDA BERBASIS WEB DI KOTAAGUNG KABUPATEN TANGGAMUS” (STUDI KASUS KEDAI LINDA KOTAAGUNG) - Rima Mawarni; Supriyanto .; Dodi Afriansyah; Linda Riyanti; Uswandi . (STMIK Dian Cipta Cendikia Kotabumi, 2022)
Internet technology has a considerable influence in all fields. The use of online transaction methods is growing rapidly, even in some aspects, and activities that were usually carried out manually are now carried out using an online system. E-commerce is increasingly in demand because of several advantages, such as relatively cheap operational costs and the ease of managing traded goods as well as the ease of preparing the required reports, because the existing data are exact data with accurate calculations. The convenience provided through e-commerce services can certainly provide benefits to all parties. There are still a lot of promotion and sales mechanisms for typical Kotaagung culinary in the conventional way, that is, buyers directly come to the shop/store that sells the food. A sales strategy like this is very likely to cause problems in the future, including customers/buyers who are located far apart or outside the city will object to shopping at the store. Management management is still done manually. The system development method used is a prototype, with UML system development tools, use case diagrams, class diagrams, sequence diagrams, activity diagrams. With the existence of online culinary sales, it is hoped that it will make it easier for shop owners to do their culinary marketing and assist in making daily or monthly income reports, so that the time used is more effective and efficient.